Numerical analysis of shock wave propagation and AL5083 sheet bulging in explosive hydro forming process - Jabalamelian, Saeed (2012)
The present work simulated the explosive forming of a torisperical dished head from the Al-5083 aluminum alloy against a male die. The simulation was used to investigate the strain distribution across the final product as well as to capture the complex nature behind this High Energy Rate Forming (HERF) technique. The study was carried out in the framework of LS-DYNA code, based on the Arbitrary Lagrangian Eulerian (ALE) Multi-Material formulation, which provided a finite element mesh that moved independently from the material flow and allowed each element to contain a mixture of two or more different materials. The underwater explosion phenomenon including the shock wave propagation and the state of detonation products was perfectly simulated using the Jones-Wilkins-Lee (JWL) and Gruneisen equations of state for explosive and water, respectively. The results were validated based on the Cole’s experimental and analytical works on underwater explosion of relatively small charge, which showed the average error of 6.4%. The simulation outcomes showed that the primary shock could be modified by accelerating the specimen up to 100 m/s and reflecting back toward the water, which could lead to cavitations. The formation of the cavitations and their effects on the deformation of the specimen were investigated numerically; same as the other aspects of the desired process. Since many of these phenomena were too difficult to be investigated experimentally, a comprehensive understanding of the Explosive Hydro Forming (EHF) process was achieved through a numerical simulation in this study. The behavior of the specimen under explosive loading was predicted according to the Johnson-Cook (JC), Modified Zerilling-Armstrong (MZA) and Plastic-Kinematic (PK) constitutive equations, which were used to investigate the strain distribution across the final product. Moreover, three techniques were examined numerically involving increasing the ratio between the thickness and diameter of sheet plate, using the sheet holder and grooving the edge of the workpiece to reduce the wrinkling at the edge of the workpiece.